2013
DOI: 10.1002/etc.2412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gold nanoparticles and ciprofloxacin on microbial catabolism: a community‐based approach

Abstract: The effect of gold nanoparticles (AuNPs) and ciprofloxacin on the catabolism of microbial communities was assessed. This was accomplished through an ex situ methodology designed to give a priori knowledge on the potential for nanoparticles, or other emerging contaminants, to affect the catabolic capabilities of microbial communities in the environment. Microbial communities from a variety of sources were incubated with 31 prespecified carbon sources and either National Institute of Standards and Technology ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…However, the data collected here demonstrate robust AMF colonization of the 76R plants compared to typical values in unexposed plants [ 6 , 11 ], despite rhizoplane accumulation. This finding, which is similar to other recent work examining the effects of Au ENMs on rhizosphere biota [ 30 ], suggests that AMF colonization may be relatively resistant to potential effects induced by at least Au ENM accumulation at the rhizoplane over the time periods tested here.…”
Section: Discussionsupporting
confidence: 91%
“…However, the data collected here demonstrate robust AMF colonization of the 76R plants compared to typical values in unexposed plants [ 6 , 11 ], despite rhizoplane accumulation. This finding, which is similar to other recent work examining the effects of Au ENMs on rhizosphere biota [ 30 ], suggests that AMF colonization may be relatively resistant to potential effects induced by at least Au ENM accumulation at the rhizoplane over the time periods tested here.…”
Section: Discussionsupporting
confidence: 91%
“…There are also studies reporting no or minimal effect of ENPs such as nZnO and nanosized zerovalent Cu, nTiO 2 , and nanosized Al 2 O 3 and SiO 2 on the soil microbial community . Weber et al showed that 10 nm citrate-coated nAu enhanced the catabolic activity of microbial communities from loamy soil . The observed impacts of applied ENPs vary depending on the composition, dose, and properties of ENPs such as coating, size, and age or physicochemical properties of the receiving soils …”
Section: Introductionmentioning
confidence: 99%
“…23 Weber et al showed that 10 nm citrate-coated nAu enhanced the catabolic activity of microbial communities from loamy soil. 37 The observed impacts of applied ENPs vary depending on the composition, dose, and properties of ENPs such as coating, size, 24 and age 38 or physicochemical properties of the receiving soils. 25 In this study, we systematically investigated the impact of metal ENPs and their dissolved ions on soil enzyme activity and microbial community composition of a biosolid-amended agricultural soil.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These concentrations were determined by a recent study which determined the annual predicated environmental concentrations of AuNPs in surface waters for the UK and US as 4.68 and 4.7 × 10 –6 ng/mL, respectively . The concentrations used in this study were several orders of magnitude higher than those predicted but still substantially lower than those often used in other nano-ecotoxicology studies which typically utilize concentrations near or above 1 mg/L Scheme illustrates the traditional protocol for C.…”
Section: Resultsmentioning
confidence: 92%
“…48 The concentrations used in this study were several orders of magnitude higher than those predicted but still substantially lower than those often used in other nanoecotoxicology studies which typically utilize concentrations near or above 1 mg/L. 49 Scheme 1 illustrates the traditional protocol for C. elegans AuNP exposure and postexposure sample processing. This approach utilizes water rinsing between centrifugation steps in an effort to remove cuticle-adsorbed AuNPs and AuNPs freely suspended in dispersion media.…”
Section: Resultsmentioning
confidence: 99%